FORMULASI KRIM MINYAK ATSIRI RIMPANG TEMU GIRING (Curcuma heyneana Val & Zijp): UJI SIFAT FISIK DAN DAYA ANTIJAMUR TERHADAP Candida albicans SECARA IN VITRO - Dewi Rahmawati; Anita Sukmawati; Peni Indrayudha (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Essential oil of Curcuma heyneana Val & Zijp has antifungal activity against Candida albicans with minimum inhibitory concentration (MIC) 0.25% v/v. Characteristic of essential oil is easy to evaporate from the skin surface. Therefore, it should be formulated in cream. The research aims to know influence of cream formulations of Curcuma heyneana oil toward physical characteristics and antifungal activity against Candida albicans. Essential oil was obtained by water and steam destillation. Cream were made into oil in water base (O/W) and water in oil base (W/O) containing 10% of Curcuma heyneana oil. Cream were tested for physical characteristics (such as viscosity, spreadability, protection ability, adhesive time, pH) and also in vitro antifungal activity against Candida albicans. Observation for antifungal activity was done after incubation for 48 hours. Data for physical characteristics and antifungal activity were analyzed using one way anava and continued with t-LSD test (p=0,95). The research indicated that W/O cream containing Curcuma heyneana oil had higher viscosity than O/W cream. Spreadability and protection ability O/W cream was better than W/O cream. Adhesive time of W/O cream was longer than O/W cream. Both of O/W and W/O cream had pH level of 6-7. O/W cream containing Curcuma heyneana oil had better inhibition zone against Candida albicans than cream W/O, they were 1.84±0.071 cm and 1.70±0.074 cm, respectively.